GAMBARAN PENYIMPANAN BAHAN MEDIS HABIS PAKAI (BMHP) DI GUDANG FARMASI RSUD PADANG PARIAMAN - Handayuni, Linda; Novita, Dian; Aini, Rafika; Fitri, Aznila (Ensiklopedia of Journal, 2023)
The storage of medical consumables in the pharmacy warehouse is an integral part of ensuring their quality and suitability before being distributed to patients. Errors in storage can damage the quality of medical consumables and result in losses for the hospital. This study aims to evaluate the management of medical consumables storage at RSUD Padang Pariaman from the perspectives of human resources, procedures, and infrastructure. The results indicate that the available human resources are adequate in terms of quantity and competency but require regular training to maintain work quality. Detailed SOPs have been developed; however, their implementation faces challenges, such as the absence of stock cards and labels on storage racks. From the perspective of infrastructure, several deficiencies were identified, including the lack of room thermometers, fire extinguishers, and storage space dividers. Based on the evaluation, corrective measures are needed, such as improving human resource competencies, enforcing SOP implementation, and providing facilities that meet the standards. With these improvements, the management of medical consumables can support optimal healthcare services.Keywords: storage, BMHP, pharmacy